2010
DOI: 10.1097/ccm.0b013e3181c9cc3b
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of thrombotic risk factors: The difficulty in using clinical trials to develop a risk assessment model

Abstract: There is a paucity of data assessing the risks and prevention of venous thromboembolism in critical care settings. Consequently, it is difficult to estimate the risk of venous thromboembolism for a typical patient, on an individual basis, and this difficulty leads to underuse of thromboprophylaxis, especially in intensive care unit patients. Thrombosis is a multifactorial disease and patients may present multiple risk factors simultaneously. The problem in quantifying risk factors is to combine these risk fact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
8
0
1

Year Published

2010
2010
2016
2016

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 57 publications
0
8
0
1
Order By: Relevance
“…Risk assessment models have been developed to facilitate clinical decision-making (2,53). Electronic alert programs based on programmed risk models have been implemented, resulting in improved prophylaxis use to a certain extent (6,(54)(55)(56). One study showed that physician alert reduced VTE incidence from 4.13 to 2.23 events per 1,000 patients (odds ratio [OR] 0.54; 95% confidence interval [CI] 0.20-1.33) (30).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Risk assessment models have been developed to facilitate clinical decision-making (2,53). Electronic alert programs based on programmed risk models have been implemented, resulting in improved prophylaxis use to a certain extent (6,(54)(55)(56). One study showed that physician alert reduced VTE incidence from 4.13 to 2.23 events per 1,000 patients (odds ratio [OR] 0.54; 95% confidence interval [CI] 0.20-1.33) (30).…”
Section: Discussionmentioning
confidence: 99%
“…immobilisation, acute medical illness, trauma, surgery, and certain therapies) risk factors (2). Medical illnesses that independently increase VTE risk include congestive heart failure (CHF), cancer, ischaemic stroke, renal and respiratory failure, hypertension, diabetes, chronic pulmonary disease, severe infection, and in-flammatory diseases (3)(4)(5)(6). Patients hospitalised for an acute medical illness carry multiple VTE risk factors, which have been reported to result in an eight-fold increase in VTE risk compared to the general population (3).…”
Section: Introductionmentioning
confidence: 99%
“…heart failure). 25 Trauma patients with co-morbidities and an increased BMI may benefit most from early initiation of LMWH or placement of an IVC filter if they have contraindications to LMWH.…”
Section: Discussionmentioning
confidence: 99%
“…Risk assessment is crucial to provide the appropriate prophylaxis to the right patients (17). The current American College of Chest Physicians (ACCP) proposes three risk categories (13): 1) low risk for medical patients who are fully mobile and for whom the estimated risk of asymptomatic DVT without thromboprophylaxis is <10%; 2) moderate risk for medical patients, those for whom bed rest is prescribed, sick patients, or patients with a moderate risk for VTE plus high risk for bleeding, corresponding to a risk of DVT without thromboprophylaxis between 10% and 40%; and 3) high risk for VTE plus a high risk for bleeding, corresponding to a risk of DVT in the absence of thromboprophylaxis ≥40%.…”
Section: Introductionmentioning
confidence: 99%